Shaking table testing of an existing masonry building: assessment and improvement of the seismic performance - Mendes, N. (2014)
This paper aims to assess and improve the seismic performance of an existing masonry building with ﬂexible ﬂoors, representative of a Portuguese building typology—‘gaioleiro’ buildings. The study involved seismic tests and dynamic identiﬁcation tests of two models (nonstrengthened and strengthened) in the shaking table. Each model was subjected to several seismic tests with increasing amplitude. . Before the ﬁrst test and after each seismic test, the dynamic identiﬁcation of the model was carried out, aiming at obtaining their seismic vulnerability curves based on a damage indicator obtained from the decrease of the frequencies of the modes. In the strengthened model, steel elements were used to improve the connection between walls and ﬂoors, together with ties in the upper stories. The results show that adopted strengthening technique is effective for reducing the seismic vulnerability of ‘gaioleiro’ buildings, namely for improving the out-of-plane behavior of the facades.